Influence of Problem Based Learning Models (PBL) and Learning Motivation to Learn Outcomes and Student's Critical Thinking Skills Themes of Caring for Life in Class IV Primary School No 026609 Pujidadi Binjai - Muhammad Rizki Utomo; Hasruddin Hasruddin; Abdul Murad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The results obtained from this study include the learning outcomes of students in the experimental class and control class, the students 'critical thinking skills in the experimental class and the control class as well as the observation data of students' learning motivation on the theme of caring for living beings in grade IV Elementary School 026609 Pujidadi Binjai in the 2019 academic year. / 2020. shows that the average score of learning motivation in the experimental class is 82.20 with a standard deviation of 6.823 and the average score of learning motivation in the control class is 45.23 with a standard deviation of 1.007. Furthermore, the results of the students' learning motivation scores between the experimental class and the control class are combined then the median is sought. This process is carried out to divide motivation into two groups, namely the high motivation group with the criteria of students with a motivation score above the middle value (median) and the low motivation group with the criteria of students with a motivation score below the middle value. As for the calculation, the median value is 63.71. The research method used is Quasi Experimental Quasi (Quasi Experimental Method) with the research design as the basis for the implementation of the research is to distinguish the effect of problem-based learning models and the effect of expository learning on student outcomes and critical thinking skills in science in terms of high learning motivation and low learning motivation. the treatment class is class V1 class V2.